Improving Compliance and Quality of Documentation of Cerebral Function Monitoring in a Neonatal Neurocritical Care Unit. Issue 5 (26th September 2021) - Goswami, Ipsita; Chansarn, Panadda; Aldana Aguirre, Jose; Taher, Floura; Wilson, Diane; Hahn, Cecil; ElShahed, Amr; Lee, Kyong-Soon
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Neonates admitted to neurocritical care units frequently undergo continuous bedside cerebral function monitoring (CFM). Documentation of CFM findings that are complete and accurate can augment the quality of care through improved communication. We aimed to increase the compliance with and quality of CFM documentation in the electronic medical records by 50% in our neonatal intensive care unit over 6 months. Methods: We used the Plan-Do-Study-Act methodology, process mapping, and fishbone analysis. We implemented interventions, including the development of standardized EMR templates, face-to-face reminders at staff meetings and clinical handover sessions, and teaching on CFM interpretation. Results: We evaluated 50 and 161 charts pre (August–October 2018) and postintervention (December 2018–July 2019), respectively. We improved compliance with documentation from 72% to 89% ( P = 0.004); and the quality of documentation from 10% to 61% ( P < 0.001). Multimodal reminders to document and educational sessions to increase familiarity with CFM interpretation effectively improved the quality of documentation. Conclusions: We improved the compliance with and the quality of CFM documentation using targeted quality improvement interventions with case-focused educational sessions, reference tools, and standardized templates. Barriers to compliance with documentation were adverse effects on the workflow that changes in the EMR system may address. A significant challenge to sustainability was the high frequency of rotating trainees. We addressed this challenge by developing mandatory electronic teaching modules that include reminders to document and a case-focused teaching curriculum; to increase awareness of the importance of CFM documentation and increase confidence in CFM interpretation.